Communal Land Protection in Betung Kuning: Toward a Tripartite Legal Harmonization - Naufal Asyirof; Widiya Yul; Rasmita Rasmita (Fakultas Syariah INSURI Ponorogo, 2026)
The protection of communal land remains a critical issue in Indonesia due to the gap between customary recognition and formal legal certainty. This study examines communal land governance through the Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) No. 14 of 2024 from the perspective of Islamic family law. Using an empirical qualitative approach, data were collected through interviews, observation, and document analysis in Betung Kuning Village. The findings reveal that communal land is socially recognized under customary law but largely unregistered, leading to boundary disputes, inheritance conflicts, weak legal standing, and limited economic utilization. From the perspective of Islamic family law, land registration is essential to ensure clarity of inheritance assets, protect heirs’ rights, and promote distributive justice in line with the principle of ḥifẓ al-māl. Although the regulation represents a progressive legal framework, its implementation faces challenges, including legal fragmentation, low legal literacy, limited historical documentation, financial constraints, and cultural resistance. This study proposes a tripartite harmonization model integrating customary law, Islamic law, and national law to support inclusive and sustainable communal land governance.